2011
DOI: 10.1038/cgt.2011.31
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tumor suppression by an ING4/IL-24 bicistronic adenovirus-mediated gene cotransfer in human non-small cell lung cancer cells

Abstract: ING4 as a member of inhibitor of growth (ING) tumor suppressor family has potent inhibitory effects on a variety of tumors. Interleukin-24 (IL-24), a cytokine-tumor suppressor, also shows broad-spectrum and tumor-specific antitumor activities. In this report, we constructed an ING4/IL-24 bicistronic adenovirus (Ad-ING4-IL-24) and assessed its combined effect on in vitro and in vivo A549 human non-small cell lung cancer cells. We demonstrated that ING4 and IL-24 combination treatment by adenovirusmediated ING4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Several of the ING proteins can inhibit the growth of cancer cells in vitro and in vivo when overexpressed using adenoviral vectors [23], [24], [25], [26], [27], [28]. The ING proteins might be particularly useful to enhance chemosensitivity in combination with agents like etoposide and doxorubicin [29].…”
Section: Introductionmentioning
confidence: 99%
“…Several of the ING proteins can inhibit the growth of cancer cells in vitro and in vivo when overexpressed using adenoviral vectors [23], [24], [25], [26], [27], [28]. The ING proteins might be particularly useful to enhance chemosensitivity in combination with agents like etoposide and doxorubicin [29].…”
Section: Introductionmentioning
confidence: 99%
“…These findings revealed that ING4 may attenuate the growth of various tumors. Numerous studies have shown that cancers such as brain tumors, gastric carcinoma, lung cancer, head and neck squamous cell carcinoma, malignant melanoma, hepatocellular carcinoma and ovarian carcinoma could be inhibited by ING4 as a result of its multimodal tumor suppressive ability. In addition, ING4 can enhance the sensitivity of various cancer cells to chemotherapeutic agents, such as doxorubicin and etoposide.…”
Section: Therapeutic Genes For Cns Diseasesmentioning
confidence: 99%
“…Extensive studies have shown that IL-24 displays ubiquitous antitumor property and tumor-specific killing activity [97]. ING4/IL-24 bicistronic adenovirus (Ad-ING4-IL-24) combination treatment was shown to have a synergistic tumor-suppressive capacity in NSCLC, breast cancer and hepatocarcinoma and promote radiosensitivity of breast cancer cells [98][99][100][101]. …”
Section: Ing4 In Cancer Therapymentioning
confidence: 99%